Islamic religious learning and society: analytical review - Bensaid, Benaouda; Bentahar, Saleh (2012)
This paper sheds light on the position and role of religious learning on the making of contemporary societies, impact on sustainable development. the prospects and impediments affecting their mutual interaction and the quality of their synchrony. Such a research opens up new fields of inquiry in regards to the position of religious learning in current social and intellectual progress, and the current debates and reviews of religious curriculum and development.